Professional JavaScript for web developers - Zakas, Nicholas C. ([Place of publication not identifed] : John Wiley & Son, Inc., 2012)
A significant update to a bestselling JavaScript book As the key scripting language for the web, JavaScript is supported by every modern web browser and allows developers to create client-side scripts that take advantage of features such as animating the canvas tag and enabling client-side storage and application caches.
Script for web developers /, Professional
Keywords: WEB SITE DEVELOPMENT